The Semiannual and 4.4‐Year Modulations of Extreme High Tides. Issue 8 (4th August 2019) - Ray, R. D.; Merrifield, M. A.
Abstract: In most places extreme high tides undergo a clear seasonal variation. It is well known that semidiurnal tides tend to peak during equinox seasons, and diurnals during solstice seasons. This is a consequence of the solar and lunar declinations, which when large maximize diurnal tides at the expense of semidiurnals. The semiannual range modulation of tidal extremes for a pure semidiurnal tide is determined mainly by the amplitude of the K2 constituent; a pure diurnal is determined mainly by P1 . Mixed tidal regimes tend to experience maxima very roughly around the times of solstice, but not always, with the semiannual modulation generally a complicated function of constituent amplitudes and phases. These modulations are here mapped worldwide by analyzing tidal extremes predicted with a global tide model. The known 4.4‐year modulation in extreme tides is a consequence of declinational and perigean effects coming in and out of phase. The phase of the 4.4‐year modulation is controlled by the phase of the semiannual modulation, irrespective of whether the tide is diurnal, semidiurnal, or mixed. Key Points: Range and timing of semiannual and 4.4‐year modulations in extreme high tides are mapped globally Semiannual phase is trivial for purely diurnal or semidiurnal tides but otherwise is complicated function of constituent amplitudes/phases The phase of the semiannual modulation controls the phase of the 4.4‐year modulation